THE IMPORTANCE OF USING DESIGN THINKING METHODOLOGY IN TEACHING ENGLISH - Rajabova, Muniskhon (Innovative Development in Educational Activities, 2024)
This article explores the integration of design thinking methodology in English language teaching, emphasizing its impact on creativity, critical thinking, and language acquisition. Drawing insights from related research and analysis of its application, the article highlights enhanced creativity, critical thinking development, improved language acquisition, increased student engagement, and holistic skill development as key outcomes. The methodology includes a comprehensive literature review, case studies, and educator interviews. By examining the importance of design thinking in the English language classroom, the article aims to guide educators in creating dynamic and effective learning environments.